Gross Anatomical and Morphometry Studies on the Oscoxae of Indian Fox (Vulpes bengalensis (Shaw 1800)) - Vaddi, Karunasri; Botlagunta, Supriya; Ankem, Prashanth Babu; Sai Urmila, T. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during January, 2024 at the department of Veterinary Anatomy, College of Veterinary Science, Proddatur, Andhra Pradesh, India to document the anatomical details of oscoxae in Indian Fox (Vulpes bengalensis) that died due to natural causes. The bones were collected by fresh water maceration technique. The gross anatomy of bones of pelvic limb was studied after fresh water maceration and cleaning. The oscoxae of Indian fox was found to be similar in structure and number to other carnivores that have been studied. Oscoxae, the bone of pelvic girdle showed a prominent psoas tubercle on the on the caudal half of ventral border in ilium, a less conspicuous caudal ventral iliac spine cranial to the acetabulum, tuber ischii was single, incomplete acetabular rim. The mean weight and mean length of the bone were 7.41 g and 7.2 cm respectively. Cranio-dorsal to the sacropelvic surface in ilium a small eminence, the iliac tuberosity was observed. The mean length of the ilium was 4.1 cm. The greatest breadth across the coxal tuberosity was 4 cm. Pelvic symphysis contained pubis and ischium. The blunt ischiatic spine and joined with the acetabulum. The mean length of the ischium was 2.7 cm. The obturator foramen was relatively large and oval. The mean sagittal length and breadth of obturator foramen was 1.5 and 1.2 cm. The mean length and breadth of the acetabulum was 1.3 cm and 1 cm respectively. The tuber ischii was single.